Lack of Emotional Experience, Resistance to Innovation, and Dissatisfied Musicians Influence on Music Unattractive Education - Zhang, Dongjun; Akhter, Shamim; Kumar, Tribhuwan; Nguyen, Nhat Tan (Frontiers in Psychology, 2022)
Music education is frequently growing around the globe and needs emotional attachments and adoption innovation for the attractive music education that needs researcher’s emphasis. Thus, the current article investigates the impact of lack of emotional experience and resistance to innovation on unattractive music education in China. The current research also investigates the mediating impact of dissatisfied musicians among the association of lack of emotional experience, resistance to innovation and unattractive music education in China. The study has used the primary data collected using questionnaires. The current article examines the validity and reliability using the measurement assessment model and also tests the hypotheses using the structural assessment model with the help of smart-PLS. The results indicated that the lack of emotional experience and resistance to innovation has a positive and significant impact on unattractive music education in China. The findings also revealed that dissatisfied musicians significantly mediate among lack of emotional experience, resistance to innovation and unattractive music education in China. This article helps policymakers establish policies about making music education attractive for musicians by adopting innovation.